PENILAIAN PT BALAI PUSTAKA (PERSERO) UNTUK TUJUAN RESTRUKTURISASI TAHUN 2010 - , R.A.Y. Indriasari Sundoro; , M. Edhie Purnawan, M.A., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The aim of this study is to estimate the fair value of Balai Pustaka (State Owned Enterprise) in relation to restructuring program carried out by the Government. At the moment, Balai Pustaka is experiencing financial problems or financial distress, as indicated by the continuing net losses since 2005 and capital deficiency or negative book value equity of the firm. The result of these assessments can be used to determine wether the restructuring program capable of securing the State Capital has been invested in Balai Pustaka. Another purpose of this study is to analyze the causes of financial distress experiencing by Balai Pustaka. Both objectives are closely linked because by identifying the cause of financial distress and the remedial measures undertaken will make the selection of inputs be better for the valuation. The data analyzed in this research were obtained from financial statements of Balai Pustaka which have been audited for the Year 2004 to Year 2009, beta risk data comparison companies listed on stock exchanges in the sectors of advertising, printing, and media, data comparison company stock prices and stock index data for a period of Year 2008 to Year 2010 in order to estimate the unlevered industry beta since Balai Pustaka is a private firm. The estimated fair value of the firm is carried out using the income approach by applying the discounted cash flow method, using free cash flow to the firm model, and the asset approach by applying adjusted book value method. The estimation using discounted cash flow method has result a fair value of Rp103.436 billion or, after calculating the long-term debt the estimation of fair value of equity is Rp20.603 billion. While the estimation using adjusted book value method has resulted an estimated fair value of equity at Rp5.608 billion. Reconciliation of value by using both methods after considering their weights and lack of marketability discount (DLOM) has resulted an estimated fair value of Balai Pustakaâs equity at Rp11,798 billion or equivalent to Rp117,98 million per share.